2007
DOI: 10.5194/cp-3-569-2007
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the 1500-year climate cycles in Holocene North-Atlantic records

Abstract: Abstract. Since the first suggestion of 1500-year cycles in the advance and retreat of glaciers (Denton and Karlen, 1973), many studies have uncovered evidence of repeated climate oscillations of 2500, 1500, and 1000 years. During last glacial period, natural climate cycles of 1500 years appear to be persistent (Bond and Lotti, 1995) and remarkably regular (Mayewski et al., 1997; Rahmstorf, 2003), yet the origin of this pacing during the Holocene remains a mystery (Rahmstorf, 2003), making it one of the outsta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
150
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(180 citation statements)
references
References 22 publications
27
150
2
1
Order By: Relevance
“…In the South Atlantic, however, only the effect of the weaker circulation is registered. There may also have been more general climatic effects of the 8.2 ka event and its assumed massive fresh-water discharge: the MOC may have been influenced by different processes such as dynamics in the amount of fresh-water and sea-ice/ice bergs, atmospheric circulation variability and also internal oceanic forcing (Debret et al, 2007), although the end product in the South Atlantic was the same as during later perturbations. Another or complementary explanation may be that the 8.2 kyr event was an anomaly with a different triggering mechanism, as compared to most of the other Holocene perturbations, for which solar forcing and related feedbacks have been invoked as major players (Bond et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In the South Atlantic, however, only the effect of the weaker circulation is registered. There may also have been more general climatic effects of the 8.2 ka event and its assumed massive fresh-water discharge: the MOC may have been influenced by different processes such as dynamics in the amount of fresh-water and sea-ice/ice bergs, atmospheric circulation variability and also internal oceanic forcing (Debret et al, 2007), although the end product in the South Atlantic was the same as during later perturbations. Another or complementary explanation may be that the 8.2 kyr event was an anomaly with a different triggering mechanism, as compared to most of the other Holocene perturbations, for which solar forcing and related feedbacks have been invoked as major players (Bond et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…2f) of a reconstruction based on these four components (Fig.2e) shows that they have periods of ~6500-yr, ~2500-yr, ~950-yr and ~550-yr. Previous studies associated the last three periodicities with solar forcing (O'Brien et al 1995, Stuiver et al 1995, Mayewski et al 1997, Debret 2007.…”
Section: Solar Modesmentioning
confidence: 99%
“…Let assume that the solar forcing is transferred through the atmosphere without any significant change of his form and then reaches the ocean surface, where is rectified by the THC. For example, in For the ocean however, both, the fundamental and derived modes can be identified in the spectrum (Debret et al 2007). Consequently, coherent ocean atmosphere variations could only be associated with the fundamental modes, as only these are present in the spectra of both climate components.…”
mentioning
confidence: 99%
“…Significant correlations obtained between the stacked marine records and cosmogenic radionuclides, whose activity concentrations are thought to be modulated by the solar-terrestrial geomagnetic activity, suggested originally that changes in solar activity could be the major forcing agent of these events (Bond et al, 2001). A later study conducted on the cyclicity pattern of the time series using spectral wavelet analysis was able to distinguish between the solar forcing and the oceanic forcing to show that the 1500-year cycle was basically an ocean-related climate phenomenon (Debret et al, 2007).…”
Section: Introductionmentioning
confidence: 99%